Kekuatan dan Sumber Daya dalam Negoisasi - Raffly Firmansyah Putra; Wilchan Robain; Vira Khairunisa; Zuhairi Rangkuti; Siti Nur Fadhilah; Silverius Yoan Sihotang (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This article aims to provide a comprehensive literature review on how professional ethics can serve as an effective strategy to prevent fund misuse within organizational financial management. Professional ethics is viewed as a set of moral values, behavioral norms, and professional standards that guide financial managers to perform their duties with honesty, responsibility, and without conflicts of interest. In the context of financial management, these duties include recording, budgeting, monitoring, and reporting financial activities, all of which require accuracy and transparency. The study highlights five main principles of professional ethics: integrity, objectivity, professional competence, confidentiality, and professional behavior. These principles clarify rules, strengthen accountability, and ensure that financial processes comply with established standards. The literature review shows that applying professional ethics not only encourages individuals to act correctly but also enhances responsibility, improves performance, and strengthens financial oversight. Integrity and objectivity play a crucial role in preventing report manipulation, budget inflation, and fund misuse, as these principles demand moral courage and fair decision-making. Professional competence ensures that every financial process is carried out accurately and in accordance with regulations, while confidentiality protects sensitive information from misuse. Professional behavior emphasizes adherence to laws, organizational policies, and professional standards. The article also identifies several supporting factors that enable the effective implementation of professional ethics, such as strong internal policies, leadership commitment to integrity, an ethical workplace culture, layered supervision systems, and continuous ethics training. Conversely, common challenges include weak internal controls, limited understanding of ethics, organizational pressure, conflicts of interest, and inconsistent application of ethical standards. Therefore, this article underscores that integrating professional ethics into organizational financial policies, procedures, and management systems is a key step in preventing fund misuse and strengthening stakeholder trust in the organization’s transparency and accountability.